2023
DOI: 10.1039/d2en00933a
|View full text |Cite
|
Sign up to set email alerts
|

Efficient molecular oxygen utilization of micelle-based BiOCl for enhanced in situ H2O2 production induced photocatalytic removal of antibiotics

Abstract: Photocatalytic self-Fenton technology is regarded as a promising strategy to promote the removal of pollutants in wastewater, and the in-situ H2O2 production rate is one of the main factors affecting...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…In addition, except for the eminent abovementioned photocatalysts, some other catalysts still possess outstanding H 2 O 2 generation, which could be further investigated for the application to the PSFs and their potentials are displayed in Figure 16. [159][160][161][162][163][164][165][166][167]…”
Section: Other Admirable Photocatalystsmentioning
confidence: 99%
“…In addition, except for the eminent abovementioned photocatalysts, some other catalysts still possess outstanding H 2 O 2 generation, which could be further investigated for the application to the PSFs and their potentials are displayed in Figure 16. [159][160][161][162][163][164][165][166][167]…”
Section: Other Admirable Photocatalystsmentioning
confidence: 99%
“…Antibiotics always cause the emergence or evolution of antibioticresistant genes in aquatic microorganisms that are harmful to human health. 1,2 Among them, ofloxacin (OFL), as a fluoroquinolone antibiotic, is frequently used to treat a variety of diseases, 3 and the concentration in medical wastewater generally ranges from 25 000 ng L −1 to 35 000 ng L −1 . 4 Once it accumulates in the human body through the food chain, immunity and body organs are impaired, and it may even be damaging to life.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various semiconductor photocatalysts, the high chemical stability, low toxicity, and ease of synthesis associated with bismuth oxychloride (BiOCl) have generated substantial interest among researchers. 11,12 Moreover, BiOCl consists of [Bi 2 O 2 ] 2+ ionic layers interspersed with double Cl − layers, and this unique layered structure allows for an internal electric field. Numerous studies have shown in great detail how this internal electric field greatly facilitates the separation and migration of photogenerated charge carriers.…”
Section: Introductionmentioning
confidence: 99%